MicroRNA-582-5p Contributes to the Maintenance of Neural Stem Cells Through Inhibiting Secretory Protein FAM19A1 - Zhang, Yu-Fei; Li, Xin-Xin; Cao, Xiu-Li; Ji, Chen-Chen; Gao, Xiang-Yu; Gao, Dan; Han, Hua; Yu, Fei; Zheng, Min-Hua (Frontiers in Cellular Neuroscience, 2022)
Epigenetic regulations on the maintenance of neural stem cells (NSCs) are complicated and far from been fully understood. Our previous findings have shown that after blocking Notch signaling in NSCs in vivo, the stemness of NSCs decreases, accompanied by the downregulated expression of miR-582-5p. In the current study, we further investigated the function and mechanism of miR-582-5p in the maintenance of NSCs in vitro and in vivo. After transfecting a mimic of miR-582-5p, the formation of neurospheres and proliferation of NSCs and intermediate progenitor cells (NS/PCs) were enhanced, and the expression of stemness markers such as Sox2, Nestin, and Pax6 also increased. The results were reversed after transfection of an inhibitor of miR-582-5p. We further generated miR-582 knock-out (KO) mice to investigate its function in vivo, and we found that the number of NSCs in the subventricular zone (SVZ) region decreased and the number of neuroblasts increased in miR-582 deficient mice, indicating reduced stemness and enhanced neurogenesis of NSCs. Moreover, RNA-sequencing and molecular biological analysis revealed that miR-582-5p regulates the stemness and proliferation of NSCs by inhibiting secretory protein FAM19A1. In summary, our research uncovered a new epigenetic mechanism that regulates the maintenance of NSCs, therefore providing novel targets to amplify NSCs in vitro and to promote neurogenesis in vivo during brain pathology and aging.